(3QSGdI aj CMGOjK eNJGQIs ((3eMehO Hf ESeGYjd Hf CHj HcQ s)
(3ChdgG (B:s
(3bGd Ydjg GdUdGI hGdSdGe aVdJ Ydi GdfGS s
(3BNQgG (B:s
(3agPg KdGKeGFI hKdGKI YTQ MOjKG UMjMG Ydi hab GdQSd s
(3GdhQbI GdChdi SjFI GdJUhjQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs